Очистка стічних вод гальванічних підприємств від хрому з застосуванням ферітних сполук - Зоря, О. В.; Терновцев, О. В.; Зоря, Д. І. (Ways to Improve Construction Efficiency, 2013)
According to the investigations of waste water purification of electroplanting industry, that contains chromium compounds, there were proposed the technological schemes of water treatment by ferritic reagent. Were turned out the conditions of recovering with the best magnetical properties.